East Europe’s Cinema Industries Since 1989: Financing Structure and Studios - Iordanova, Dina (Javnost-The Public, 1999)
The decade worth of the East European transition allows us to sum up important lessons of the stormy and profound transformation in cultural administration. The East European cultural industries were the first ones to suffer massive cuts and withdrawal of secure funding early in the 1990s. Cinema was affected most notably. In all of the East European countries filmmaking underwent volatile structural changes and was subjected to often contradictory undertakings in administration and financing. The crumbling production routines caused a creativity crisis in many filmmakers. Problems included unfair competition, deepening generation gap, and decline in feature, documentary and animation output. The concurrent crisis in distribution and exhibition led to a sharp drop in box office indicators for all productions carrying an East European label. At the same time some East European films enjoyed an international critical acclaim internationally. The volatility in East European cinema coincided with a clearly articulated period of insecurity in West European cultural policies, driven by a growing anti-American sentiment. The establishment of such pan-European funding bodies as Media 95 and Euroimage came as a reaction to the overwhelming triumph of commercialism in cinema. The share of international subsidies for filmmaking in poverty-stricken Eastern European studios quickly increased as the concept of "national cinema" gave way to a "new European" one. The article focuses on the following topics: changes in East European production schemes, the end of national cinemas, issues of co-producing with focus on Euroimage, media and commercial financing, the questions of domestic versus foreign film distribution and exhibition, and festivals.